Pembuatan Biodiesel Dari PFAD Dengan Katalis Cu-HAp: Variasi Nisbah PFAD : Metanol dan Massa Katalis - Kamarullah, Rahmat; Yelmida, Yelmida; Yusnimar, Yusnimar (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
The increasing level of human dependence on fuel oil, an active step is needed to develop alternative fuels. At present biodiesel is a reliable energy as an environmentally friendly and inexpensive alternative energy in its production. Biodiesel is a fatty acid methyl ester (FAME) made from fat / oil. In this research, PFAD (Palm Fatty Acid Destillate) is used as raw material for making biodiesel. PFAD will be converted to FAME. This esterification reaction varied the ratio of PFAD: Methanol 1: 8, 1:12, and 1:15 with a constant stirring speed of 350 rpm at a temperature of 60 ËšC for 3 hours. The presence of metalhydroxyapatite catalysts (Cu-HAp, Co-HAp, Ni-HAp, and HAp) of 0.1, 0.2 and 0.3 grams will help convert PFAD to FAME. The effect of time and type of metal-HAp on the conversion of PFAD to FAME will be the focus of the study in this study. The highest biodelic yield was obtained at the PFAD ratio: Metahonol 1:15 with a catalyst mass of 0.1 gram. The biodiesel physics test results are in accordance with SNI 04-7182-2006 which includes a density of 0.84 g / ml, viscosity of 4.8 cSt, flash point of 120 ËšC, yield of 61.48%, acid number of 0.73 mg KOH / g of oil. Based on the analysis of GC-MS (Mass Chromatography Gas), the main compounds found in the biodiesel from PFAD were Pandecanoic methyl ester 18.49%. Key Words : biodiesel, esterification, methanol, PFAD.